The Effect of Empowerment and Compensation on the Employee Performance of CV . Siliwangi Palembang - Utami, Sendi Tri; Komariah, Siti; Wadud, Muhammad (International Journal of Community Service & Engagement, 2024)
This study aims to determine the effect of empowerment and compensation on employee performance at CV Siliwangi Palembang. The data used are primary and secondary data obtained through the distribution of questionnaires and interviews. The sampling method used is a saturated sample. The data analysis technique used is multiple linear regression analysis, t-test, and coefficient of determination analysis. The results show that there is a positive and significant influence between empowerment (X1) and employee performance (Y). The results of the study obtained the value of the correlation coefficient (R) = 0.944 which shows the influence of empowerment and compensation on employee performance is very strong or close to 94.4%. Furthermore, the value of coefficient of determination (R2) is 0.891 which indicates the contribution of the independent variables (X1) and (X2) to the dependent variable (Y) of 89.1% while the remaining 10.9% can be explained or influenced by other variables not examined in this study. This research is expected to provide benefits to companies in terms of improving employee performance.